PENGARUH SELF-EFFICACY DAN DUKUNGAN SOSIAL TERHADAP KESIAPAN KERJA MAHASISWA - Niki Astria; Meiffa Herfianti (Yayasan Insani Mandiri Santani, 2026)
This study aims to determine the effect of self-efficacy and social support on the work readiness of final-year students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. This research is a quantitative descriptive study. The population in this study was 64 respondents. Data collection techniques used were observation and questionnaires. Data analysis techniques used descriptive analysis, multiple linear regression analysis, and the coefficient of determination (R2). The results of this study indicate that Self-Efficacy has a positive effect on the Job Readiness of final year students of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu with a calculated t value > t table (4.412 > 1.66980) and (sig α = 0.000 < 0.05). Social Support has a positive effect on the Job Readiness of final year students of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu with a calculated t value > t table (6.149 > 1.66980) and (sig α = 0.000 < 0.05). The results of the F test show that the calculated F value > F table is 65.688 > 3.15 with a significance value of 0.000 < 0.05, which means that Self-Efficacy and Social Support simultaneously or together have a positive and significant effect on the Work Readiness of final year students of the Faculty of Economics and Business, Muhammadiyah University of Bengkulu, thus indicating that both independent variables have an important role in increasing students' work readiness. Keywords : Self-Efficacy, Social Support, Work Readiness